Curative effect of anti-fibrosis Chinese patent medicines combined with ursodeoxycholic acid for primary biliary cholangitis: A systematic review and meta-analysis - Bi, Yufei; Shi, Ke; Chen, Jialiang; Wang, Xianbo (Frontiers in Pharmacology, 2023)
Abstract Objective: To delineate the curative effect and safety of anti-fibrosis Chinese patent medicines（CPMs) combined with ursodeoxycholic acid (UDCA) in primary biliary cholangitis (PBC)． Methods: A computerized literature search was implemented in PubMed, Web of Science, Embase, Cochrane Library, Wanfang database, VIP database, China Biology Medicine Database, as well as Chinese National Knowledge Infrastructure from their inception until August 2022. Randomized controlled trials (RCTs) were collected on the treatment of PBC with anti-fibrosis CPMs. The eligibility of the publications was assessed by the Cochrane risk-of-bias tool. Evaluation indicators consisted of clinical efficacy rate, liver fibrosis, liver function, immune function, and symptom score. Risk ratio (RR) was utilized for the assessment of evaluating dichotomous variables and the continuous variables with a 95% confidence interval (CI) were calculated by mean difference (MD). Results: Twenty-two RCTs were selected involving 1,725 patients. The findings demonstrated that anti-fibrotic CPMs combined with UDCA could improve the effective rate, liver function, liver fibrosis, immunological indicators, and clinical symptoms compared with UDCA alone (all P < 0.05). Conclusion: This work underlines that the combination of anti-fibrotic CPMs and UDCA can improve both clinical symptoms and outcomes. Nevertheless, more RCTs with high quality are needed to assess the effectiveness of anti-fibrosis CPMs for PBC.